2021
DOI: 10.1371/journal.pone.0240270
|View full text |Cite
|
Sign up to set email alerts
|

Grief reaction and psychosocial impacts of child death and stillbirth on bereaved North Indian parents: A qualitative study

Abstract: Background Grief following stillbirth and child death are one of the most traumatic experience for parents with psychosomatic, social and economic impacts. The grief profile, severity and its impacts in Indian context are not well documented. This study documented the grief and coping experiences of the Indian parents following stillbirth and child death. Methods This exploratory qualitative study in Delhi (India) included in-depth interviews with parents (50 mothers and 49 fathers), who had stillbirth or ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
21
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 44 publications
(49 reference statements)
8
21
0
5
Order By: Relevance
“…The findings of this study confirm earlier studies that have reported that bereavement leads to relationship changes [7,8,10]. The factors that influenced relationship changes in this study: shame [5,13], the unmet expectation of support [2] and mistrust [2,10] have been confirmed separately by other studies. Of the three factors that influenced the participants' social networks, shame/stigma has received the most attention in stillbirth research.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The findings of this study confirm earlier studies that have reported that bereavement leads to relationship changes [7,8,10]. The factors that influenced relationship changes in this study: shame [5,13], the unmet expectation of support [2] and mistrust [2,10] have been confirmed separately by other studies. Of the three factors that influenced the participants' social networks, shame/stigma has received the most attention in stillbirth research.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to earlier studies [2,10], our findings also suggest that women rely more on family networks than any other types of relationships. In stillbirth bereavement, women may have no other choice but to rely on their family and existing social networks due to stigma and lack of social recognition of stillbirth loss.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations